Lucrările practice – instrument de motivare pentru studierea matematicii în clasele liceale, profil umanist [Articol] - Borş, Valeria (USARB, 2022)
One of the major problems facing maths teachers is the lack of motivation in students, the lack of interest in maths classes, the negative attitude toward everything proposed in maths classes. A very good instrument for motivating the study of mathematics is practical work. The article contains the description of three practical works performed at the mathematics courses at the "Ion Creanga" Pedagogical College in Balti.
Keywords: curriculum; motivation; practical work; mathematical skills